2014
DOI: 10.3899/jrheum.131337
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Clinical Symptoms in Diagnosing Temporomandibular Joint Arthritis in Juvenile Idiopathic Arthritis

Abstract: Despite a relatively high specificity, clinical examination alone does not seem sufficiently sensitive to adequately detect TMJ arthritis. Thus, a relatively high number of cases will be missed or overdiagnosed, potentially leading to undertreatment or overtreatment. Gd-MRI may support correct diagnosis, thereby helping to prevent undertreatment or overtreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 34 publications
(33 reference statements)
7
62
0
11
Order By: Relevance
“…The TMJ is among the most frequently affected joint in JIA patients. Prevalence of TMJ damage has been reported to be 30%‐87%, depending on diagnostic criteria and on methodology . Although TMJ damage in JIA is frequently asymptomatic, this joint may be affected both uni‐ and bilaterally, may be the first joint affected or may be affected during the course of JIA …”
Section: Introductionmentioning
confidence: 99%
“…The TMJ is among the most frequently affected joint in JIA patients. Prevalence of TMJ damage has been reported to be 30%‐87%, depending on diagnostic criteria and on methodology . Although TMJ damage in JIA is frequently asymptomatic, this joint may be affected both uni‐ and bilaterally, may be the first joint affected or may be affected during the course of JIA …”
Section: Introductionmentioning
confidence: 99%
“…29 In contrast, routine MRI is of less clinical value in patients with TMJ arthritis-related signs and symptoms, since only a limited association is shown between orofacial symptoms and TMJ MRI findings. 20,[30][31][32][33] Supporting this, Arabshahi et al 31 found no association between clinical improvements in maximal mouth-opening capacity and resolution of MRI effusion at follow-up after TMJ arthritis treatment with intra-articular steroid injections. From a clinical point of view, this means that patients with TMJ arthritis-related orofacial signs and symptoms may present no MRI indications of TMJ inflammation.…”
Section: Stoustrup and Koosmentioning
confidence: 91%
“…In this issue of The Journal, Koos, et al present results of their study about development of a clinical score for diagnosis of TMJ arthritis in patients with JIA 13 . The score is based on 5 well-defined clinical items, which were tested as single items as well as in all possible combinations.…”
Section: Rheumatologymentioning
confidence: 99%